España en la encrucijada de 1939 : exilios, cultura e identidades / Mónica Jato Brizuela, José Ángel Ascunce Arrieta, María Luisa San Miguel Casillas - Ascunce Arrieta, José ÁngelSan Miguel, Maria Luisa; Jato Brizuela, Mónica (Letras / Universidad de Deusto; 23)
Bibliografía por capítulos